PT. Jaso Malindo Perspective of Fiqh Muamalah and Law No.13 of 2003 (Case Study of PT Jaso Malindo Department of Solok-Padang) - Jenny Rahmad; Islam Hannah; Charvet Joanna (Sharia Oikonomia Law Journal, 2023)
This study raises the issue of the payment of driver wages by Induk samang (owner of PT Jaso Malindo) in Koto Baru, Kubung District, Solok Regency). As for the questions of this research, namely: first, how is the payment of driver wages made by PT Jaso Malindo in Koto Baru? Second, how is the Fiqh Muamalah Review of the Wage Payment Mechanism by PT Jaso Malindo in the form of gratuities? To answer these research questions, the authors conducted field research using data collection techniques, the authors went directly to the field to collect the necessary data, by conducting interviews with parties related to this problem, namely the driver and owner of PT Jaso Malindo company in Koto Baru District of Kubung, Solok Regency. To manage the data obtained by the author using a qualitative descriptive method. The purpose of this research is to find out the method and system of wage payments made by PT Jaso Malindo. To find out how the Muamalah Fiqh Review of wage payments is based on gratuities. The author uses a qualitative descriptive method, namely by collecting data in the field and then analyzing it. The subject or data source was obtained from the owner of PT Jaso Malindo and the drivers. Data collection techniques in this study were observations, interviews, and documentation which were analyzed descriptively qualitatively. From the research conducted, it can be concluded that PT Jaso Malindo pays wages for drivers at PT Jaso Malindo. The wages given by PT Jaso Malindo to drivers are in the form of gratuities, 18% for drivers and 82% for master samang. The maximum number of passengers on the bus is 15 people with a fare from Padang to Solok Rp.